Mengungkap Potensi Wisata Syariah Berbasis Ekonomi Lokal: Katalisator Kebangkitan Ekonomi Masyarakat Pesisir di Provinsi Lampung - Madnasir, Madnasir; Marwin, Marwin; Hanif, Hanif; Susanto, Is (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to analyze the potential of local economy-based Sharia tourism in the coastal area of Lampung and its contribution to improving the local community’s economic welfare. This study also explored the role of infrastructure, digital promotion, and local community involvement in the development of Sharia tourism. Methodology: This study used a qualitative approach with in-depth interview methods, questionnaire surveys, participant observation, and documentation. The data were analyzed using thematic analysis techniques to identify the contributions and challenges in the development of Sharia tourism. Results: The results of this study indicate that Sharia tourism has a positive impact on the economic welfare of coastal communities through increased income, job creation, and SME development. Adequate infrastructure and digital promotion significantly increased the interest of Muslim tourists, especially millennials. Local community involvement in destination management plays an important role in maintaining the sustainability of the local economy. Limitations: This study is limited to the coastal area of Lampung and uses samples that are not taken randomly, so the results may not fully represent the conditions of Sharia tourism in other areas. In addition, this study is cross-sectional and lacks longitudinal data to show the long-term impact of Sharia tourism. Contribution: This study adds to the literature on local economy-based Sharia tourism development by providing empirical evidence on the economic impacts generated. These findings support the theory of sustainable development and highlight the importance of infrastructure, digital promotion, and local community involvement as key factors in creating a sustainable and highly competitive tourism ecosystem in coastal areas.